2014
DOI: 10.1136/bmjopen-2014-005294
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy issues in the care of Chinese American immigrants with diabetes: a qualitative study

Abstract: Results: Eight key themes were found to potentially affect Chinese immigrants' capacity to obtain, communicate, process and understand diabetes related health information and consequently alter their decision making in self-care. Among the themes, three major categories emerged: cultural factors, structural barriers, and personal barriers. Conclusions:Findings highlight the importance of cultural sensitivity when working with first-generation Chinese immigrants with diabetes. Implications for health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 24 publications
1
58
1
Order By: Relevance
“…Many cultures are hierarchical in nature, with health practitioners having elevated, respected positions. For example, Chinese people will often refrain from asking health practitioners questions, believing that asking questions is impolite as it is perceived as "challenging doctors and nurses" or "putting burden on these professionals" [29]. A similar phenomenon was observed in many Chinese societies including Hong Kong, Taiwan and Chinese communities in Los Angeles, USA [29].…”
Section: Traditional Vs Western Cultures: Dissimilarities In Health mentioning
confidence: 95%
See 1 more Smart Citation
“…Many cultures are hierarchical in nature, with health practitioners having elevated, respected positions. For example, Chinese people will often refrain from asking health practitioners questions, believing that asking questions is impolite as it is perceived as "challenging doctors and nurses" or "putting burden on these professionals" [29]. A similar phenomenon was observed in many Chinese societies including Hong Kong, Taiwan and Chinese communities in Los Angeles, USA [29].…”
Section: Traditional Vs Western Cultures: Dissimilarities In Health mentioning
confidence: 95%
“…For example, Chinese people will often refrain from asking health practitioners questions, believing that asking questions is impolite as it is perceived as "challenging doctors and nurses" or "putting burden on these professionals" [29]. A similar phenomenon was observed in many Chinese societies including Hong Kong, Taiwan and Chinese communities in Los Angeles, USA [29]. Cultural preferences and lack of understanding of Western medicine can lead to delays in the diagnosis of important health conditions.…”
Section: Traditional Vs Western Cultures: Dissimilarities In Health mentioning
confidence: 97%
“…Such monitoring could include assessment of medications adherence or cultural perceptions/acceptance regarding available therapies. 39 Protective associations noted for speakers with limited English proficiency compared with English speakers in the more complex disease groups compared with the DM-only group (ie, HbA1c at the index date in the DM ϩ DEP group and trajectory differential for the DM ϩ CVD group) may reflect more intensive monitoring or increased access to and effectiveness of culturally appropriate enabling services.…”
Section: Discussionmentioning
confidence: 99%
“…In some developing countries, lack of a health insurance system was one of the predictors of irrational antibiotic use (71). Also, low insurance cover may affect migrants' access to health information (211,212). This suggests that the uptake of private insurance coverage could be a socio-economic indicator among migrant populations.…”
Section: Private Health Insurance Coveragementioning
confidence: 99%
“…Therefore, doctors, adult children, local television, spouse, local newspaper and radio were the most important health information sources (214). It has been reported that Chinese migrants in the USA found the translation of health education materials to be culturally and linguistically inappropriate and hence of limited use (211). It is important to understand the ways that migrants seek and access health information, also, the quality of health information accessed through various sources, including family and friends and online searching, should be further studied.…”
Section: Channels Of Health Information Seekingmentioning
confidence: 99%